TO WHAT EXTENT DO GLOBAL TERRORISM AND ORGANISED CRIMINALITY CONVERGE?: GENERAL PARAMETERS AND CRITICAL SCENARIOS (Journal of the Spanish Institute for Strategic Studies, 2013)
To what extent do global terrorism and organised criminality converge?: general parameters and critical scenarios Despite their differences in terms of motivations and methods, historical examples indicate that terrorism and organized criminality can converge in several ways. Indeed, some analysts think that both threats can no longer be studied in isolation. This report explores the hypothesis of a crime-terror nexus for the special case of global (jihadi) terrorism. Three types of convergence are examined: involvement in criminal activities by terrorists, transformation of terrorists groups into hybrid or purely criminal organizations and cooperation between organized criminal organizations and terrorist groups. Finally, the study ends with a section dedicated to the cases of Af-Pak, Iraq and Western Sahel, presented as examples of privileged scenarios for interaction between global terrorism and organized crime.